Biased by success and failure: How unemployment shapes stated locus of control - Malte Preuss; Juliane Hennecke (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Due to its extraordinary explanatory power for individual behavior, the interest in the concept of locus of control (LOC) has increased substantially within applied economic research. But, even though LOC has been found to affect economic behavior in many ways, the reliability of these findings is at risk as they commonly rely on the assumption that LOC is stable over the life course. While absolute stability has been generally rejected, the extent to which LOC and thus personality changes is, nonetheless, strongly debated. We contribute to this discussion by analyzing the effect of unemployment on LOC. Based on German panel data, we apply a difference-in-difference approach by using an involuntary job loss as trigger for unemployment. Overall, we find a significant shift in stated LOC due to unemployment. Because the effect is observable during unemployment only and not heterogeneous with respect to individual characteristics or unemployment duration, we conclude that only the stated LOC is biased during unemployment but the underlying personality trait itself is not affected.
Keywords: C83; J24; J64; J65; 330; personality; locus of control; unemployment; measurement error